Ectodermal Dysplasia with Amastia: A Case of One-Step Reconstruction. (4th May 2009) - Klinger, M.; Caviggioli, F.; Banzatti, B.; Fossati, C.; Villani, F.
Abstract : Background . Female patients presenting amastia associated with ectodermal dysplasia are not frequently encountered, but they are of great clinical interest and surgically demanding. Traditionally, skin alterations related to Ectodermal Dysplasia have addressed plastic surgeons to perform a two-stage approach in amastia associated with this congenital pathologic condition. This article describes an alternative method for correcting this deformity trough a mammary reconstruction in one surgical stage. Materials and Methods . We report a case of 26-year-old female patient with bilateral amastia associated with ectodermal dysplasia. Amastia in this patient was treated with implantation of subpectoral silicone gel prostheses, without previously breast tissue expansion. Results . At 18 months of follow-up after surgey, there were no complications and excellent cosmetic results were achieved. Patient and surgeon satisfaction was high and the patient underwent a bilateral areola-tattoo. Conclusions . One-stage mammary reconstruction have showed to be a reliable and effective technique also when amastia is associated with Ectodermal Dysplasia, suggesting a still satisfying biomechanical performance of the skin in this pathology.